Environmental exposure to metallic pollution impairs honey bee brain development and cognition - Monchanin, Coline; Drujont, Erwann; Le Roux, Gaël; Lösel, Philipp; Barron, Andrew B.; Devaud, Jean-Marc; Elger, Arnaud; Lihoreau, Mathieu (Journal of hazardous materials, 2024)
Laboratory studies show detrimental effects of metallic pollutants on invertebrate behaviour and cognition, even at low levels. Here we report a field study on Western honey bees exposed to metal and metalloid pollution through dusts, food and water at a historic mining site. We analysed more than 1000 bees from five apiaries along a gradient of contamination within 11 km of a former gold mine in Southern France. Bees collected close to the mine exhibited olfactory learning performances lower by 36% and heads smaller by 4%. Three-dimensional scans of bee brains showed that the olfactory centres of insects sampled close to the mine were also 4% smaller, indicating neurodevelopmental issues. Our study raises serious concerns about the health of honey bee populations in areas polluted with potentially harmful elements, particularly with arsenic, and illustrates how standard cognitive tests can be used for risk assessment.